h - Daniilidis, Kostas; Maragos, Petros; Paragios, Nikos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The six-volume set comprising LNCS volumes 6311 -- 6316 constitutes the refereed proceedings of the 11th European Conference on Computer Vision, ECCV 2010, held in Heraklion, Crete, Greece, in September 2010. The 325 revised papers presented were carefully reviewed and selected from 1174 submissions. The papers are organized in topical sections on object and scene recognition; segmentation and grouping; face, gesture, biometrics; motion and tracking; statistical models and visual learning; matching, registration, alignment; computational imaging; mutli-view geometry; image features; video and event characterization; shape representation and recognition; stereo; reflectance, illumination, color; medical image analysis.
Spotlights and Posters W2 -- Towards Computational Models of the Visual Aesthetic Appeal of Consumer Videos -- Object Recognition Using Junctions -- Using Partial Edge Contour Matches for Efficient Object Category Localization -- Active Mask Hierarchies for Object Detection -- From a Set of Shapes to Object Discovery -- What Does Classifying More Than 10,000 Image Categories Tell Us? -- Modeling and Analysis of Dynamic Behaviors of Web Image Collections -- Non-local Characterization of Scenery Images: Statistics, 3D Reasoning, and a Generative Model -- Efficient Highly Over-Complete Sparse Coding Using a Mixture Model -- Attribute-Based Transfer Learning for Object Categorization with Zero/One Training Example -- Image Classification Using Super-Vector Coding of Local Image Descriptors -- A Discriminative Latent Model of Object Classes and Attributes -- Seeing People in Social Context: Recognizing People and Social Relationships -- Discovering Multipart Appearance Models from Captioned Images -- Voting by Grouping Dependent Parts -- Superpixels and Supervoxels in an Energy Optimization Framework -- Segmentation -- Convex Relaxation for Multilabel Problems with Product Label Spaces -- Graph Cut Based Inference with Co-occurrence Statistics -- Ambrosio-Tortorelli Segmentation of Stochastic Images -- Multiple Hypothesis Video Segmentation from Superpixel Flows -- Object Segmentation by Long Term Analysis of Point Trajectories -- Spotlights and Posters R1 -- Exploiting Repetitive Object Patterns for Model Compression and Completion -- Feature Tracking for Wide-Baseline Image Retrieval -- Crowd Detection with a Multiview Sampler -- A Unified Contour-Pixel Model for Figure-Ground Segmentation -- SuperParsing: Scalable Nonparametric Image Parsing with Superpixels -- Segmenting Salient Objects from Images and Videos -- ClassCut for Unsupervised Class Segmentation -- A Dynamic Programming Approach to Reconstructing Building Interiors -- Discriminative Mixture-of-Templates for Viewpoint Classification -- Efficient Non-consecutive Feature Tracking for Structure-from-Motion -- P2?: A Minimal Solution for Registration of 3D Points to 3D Planes -- Boosting Chamfer Matching by Learning Chamfer Distance Normalization -- Geometry Construction from Caustic Images -- Archive Film Restoration Based on Spatiotemporal Random Walks -- Reweighted Random Walks for Graph Matching -- Rotation Invariant Non-rigid Shape Matching in Cluttered Scenes -- Loosely Distinctive Features for Robust Surface Alignment -- Accelerated Hypothesis Generation for Multi-structure Robust Fitting -- Aligning Spatio-Temporal Signals on a Special Manifold -- Supervised Label Transfer for Semantic Segmentation of Street Scenes -- Category Independent Object Proposals -- Photo-Consistent Planar Patches from Unstructured Cloud of Points -- Contour Grouping and Abstraction Using Simple Part Models -- Dynamic Color Flow: A Motion-Adaptive Color Model for Object Segmentation in Video -- What Is the Chance of Happening: A New Way to Predict Where People Look -- Supervised and Unsupervised Clustering with Probabilistic Shift -- Depth-Encoded Hough Voting for Joint Object Detection and Shape Recovery -- Shape Analysis of Planar Objects with Arbitrary Topologies Using Conformal Geometry -- A Coarse-to-Fine Taxonomy of Constellations for Fast Multi-class Object Detection -- Object Classification Using Heterogeneous Co-occurrence Features -- Converting Level Set Gradients to Shape Gradients -- A Close-Form Iterative Algorithm for Depth Inferring from a Single Image -- Learning Shape Segmentation Using Constrained Spectral Clustering and Probabilistic Label Transfer -- Weakly Supervised Shape Based Object Detection with Particle Filter -- Geodesic Shape Retrieval via Optimal Mass Transport -- Spotlights and Posters R2 -- Image Segmentation with Topic Random Field.
Keywords: Computer science; Computer software; Computer vision; Computer graphics; Optical pattern recognition; Biometrics; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Pattern Recognition; Biometrics; Computer Graphics; Algorithm Analysis and Problem Complexity